Coordination Between the Plantation Service and the Agricultural Service in Increasing Coffee Production in Bebesen Subdistrict, Central Aceh Regency - Berumah Rungke; Siti Hazzah Nur R (Jurnal Kebijakan Publik, 2026)
This study aims to analyze the coordination between the Plantation Office and the Agriculture Office in efforts to increase coffee production in Bebesen District, Central Aceh Regency. The method used is a qualitative approach, with data collection techniques through interviews, observations, and documentation. This research applies the coordination indicators by Hasibuan (2011:88), which include four main indicators: cooperation, communication, division of labor, and discipline. 0The research findings indicate that inter-agency coordination has been established quite effectively. In terms of cooperation, the relevant agencies have demonstrated an adequate understanding of their respective duties, supported by the educational backgrounds of agricultural officers and extension workers that align with their field of work. The communication indicator also shows positive results, as information from the agencies to farmer groups is conveyed clearly and easily understood. Regarding the division of labor, agencies perform their duties and functions according to regional regulations, and their personnel are competent in carrying out their responsibilities. Finally, in terms of discipline, agencies operate in accordance with procedures outlined in the Regent Regulation of Central Aceh, which governs the duties and functions of both the Plantation Service and the Agriculture Service. Although coordination has been well established, the agencies need to maintain and further enhance their performance, considering that coffee production has not yet reached its optimal level.